Teachers’ Code Mixing and Code Switching: Insights on Language Barriers in EFL Classroom - Rafqi Awlia Siddiq; Martin Kustati; Luli Sari Yustina (AT-TA'LIM, 2020)
This study aims to investigate code mixing and code switching used by English teachers in EFL classrooms. There are two major focuses in this study; the type of dominant code mixing and code switching used by the teachers. A qualitative study was used where the data were teachers’ language classroom gained by observing their classroom practices and utterances obtained through in-depth interviews. The result shows that there were three kinds of code mixing found in teachers’ and students’ utterances in EFL classroom. They were intra-sentential code mixing, intra-lexical code mixing, and pronunciation shifting. The study also found that there were four kinds of code switching found in teachers’ and students’ utterances. They were random mixing, English-Indonesian translation or vice versa, English precedes Indonesian or vice versa, and English sentences precede Indonesian sentences or vice versa. It indicated that code mixing and code switching cannot be separated in English language teaching and learning process. This study has proved that the English teachers used code mixing and code switching in teaching speaking in some types.